Alcohol and violent behavior among football spectators: An empirical assessment of Brazilian's criminalization. (December 2017) - Nepomuceno, Thyago Celso C.; de Moura, Jadielson Alves; e Silva, Lúcio Câmara; Cabral Seixas Costa, Ana Paula
Abstract: The relationship between alcohol and the violent behavior, expressed as branches of hooliganism, is receiving considerable theoretical attention in social and psychological literature along the past decades while empirical researches on that matter are taken for granted. The falling in appreciate such empirical approach relies on the difficult it requires to compare of two different realities; one with alcohol intake and another without it, in order to evaluate whether it might drive sport spectators into a violent behavior, holding everything else constant. This work provides such robust statistical assessment taking into consideration a Brazilian state law 13748 of April 2009, which prohibited the sale of alcoholic beverages in Pernambuco's football stadiums. We consider the effectiveness of alcohol intervention on hooligan behavior by means of non-parametric test and a autoregressive moving average series, resorting to over ten years of data (before and during the criminalization) with regard aggression and unruly conduct committed by fans before in football matches within 3 miles from the stadium. Our results bring support to the decision of Pernambuco State Legislature to abolish in January 2016 the law in favor of the legalization of alcoholic beverages sales.